1978
DOI: 10.1002/1097-0142(197805)41:5<2055::aid-cncr2820410554>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and pathologic findings in a kindred with hereditary sarcoma breast cancer, brain tumors, leukemia, lung, laryngeal, and adrenal cortical carcinoma

Abstract: A familial cancer aggregation comprising sarcomas, brain tumors, leukemias, and carcinomas of breast, larynx, lung, adrenal cortex, and other sites has been studied from a pathologic-genetic standpoint. Based upon sibships segregating for cancer, the genetic segregation parameter is estimated to be 45.6 f 11% which is compatible with that expected for a rare deleterious autosomal gene showing complete dominance. Pathologic review of 16 tumors by bright field microscopy revealed variable occurrences of intranuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

1978
1978
2000
2000

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(36 citation statements)
references
References 17 publications
0
34
0
2
Order By: Relevance
“…Members of the 4 families initially reported have been followed up for a number of years and further cancers have developed (Li & Fraumeni, 1982). Other kindreds showing a similar array of tumours have been reported (Bottomly et al, 1971;Lynch et al, 1978;Blattner et al, 1979;Pearson et al, 1982;Duncan & Miller, 1983), and it has been suggested that there is a role for surveillance programmes aimed at early diagnosis and treatment amongst these families (Li & Fraumeni, 1975, 1982. However, all these kindreds have been ascertained by chance, or by investigating the extended pedigree of cases with a known family history of cancer, for example, sibling pairs of soft tissue sarcoma.…”
mentioning
confidence: 99%
“…Members of the 4 families initially reported have been followed up for a number of years and further cancers have developed (Li & Fraumeni, 1982). Other kindreds showing a similar array of tumours have been reported (Bottomly et al, 1971;Lynch et al, 1978;Blattner et al, 1979;Pearson et al, 1982;Duncan & Miller, 1983), and it has been suggested that there is a role for surveillance programmes aimed at early diagnosis and treatment amongst these families (Li & Fraumeni, 1975, 1982. However, all these kindreds have been ascertained by chance, or by investigating the extended pedigree of cases with a known family history of cancer, for example, sibling pairs of soft tissue sarcoma.…”
mentioning
confidence: 99%
“…Germ-line mutations in TP53 are associated with Li-Fraumeni syndrome (18,19), and RCND has several clinical features in common with Li-Fraumeni syndrome (15,40,41) making TP53 a potential candidate for RCND. To date, no polymorphisms within canine TP53 have been reported; thus, to determine the position of TP53 relative to RCND and the other markers on CFA5, we constructed an RH map of CFA5.…”
Section: Resultsmentioning
confidence: 99%
“…LiFraumeni disease is characterized by a wider array of early onset tumors than is observed in RCND, including sarcomas, leukemias, and later in life, breast cancer (40,41). TP53 has not been associated with any polymorphisms in dogs and thus can be placed only on the RH map, whereas RCND is localized on the linkage map.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of one possible SBLA (sarcoma, breast, brain, laryngeal, lung, adrenocortical cancer and leukaemia, Lynch et al, 1978) family (no. 18), there were no cases of known familial cancer (multiple endocrine neoplasia, polyposis coli).…”
Section: Resultsmentioning
confidence: 99%